Evaluating performance by using the ABC model improves municipal services - Khawla Hadi Atiwi; Salem Awad Hadi (Journal of Madenat Alelem University College, 2018)
The objective of the research is to study the concept and objectives of evaluating the performance and modern models adopted under the variables of the modern business environment, and to clarify the system of activities ABC as one of these modern models in evaluating the performance that leads to improvement of services in the municipality. Of the budget allocation does not correspond to the percentage of actual costs of the activities carried out by the allocation, the proportion of costs exceeded the percentage of completion, partly because of weak planning for the lack of participation of stakeholders in the preparation of planning budget, especially absence of the role of cost accountant for the country's lack The cost of the system as well as the lack of activation of fines, The researcher recommended the need to prepare budgets on the basis of activities in quantities and amounts to achieve effective control of activity and proper planning to reduce the deviations and reliance on the cost system in the preparation of these budgets as well as matching the ratios of costs with the ratios of quantities achieved and the activation of fines and follow-up to their role in reducing costs, The basis of